(untitled) (Conferencea, 2024)
One of the most interesting phenomena that has provided a lot of information about defects in single crystals is photoluminescence (PL). This paper presents data on edge and near-infrared (IR) luminescence of layered GeS single crystals. In the layered high-resistivity semiconductor compound GeS, local centers have been studied using both photoelectric and optical methods. Comprehensive studies of photoelectric and optical properties indicate that the recombination scheme of GeS is quite complex and contains a number of local levels.